If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-6)/11=-2
We move all terms to the left:
(x-6)/11-(-2)=0
We add all the numbers together, and all the variables
(x-6)/11+2=0
We multiply all the terms by the denominator
(x-6)+2*11=0
We add all the numbers together, and all the variables
(x-6)+22=0
We get rid of parentheses
x-6+22=0
We add all the numbers together, and all the variables
x+16=0
We move all terms containing x to the left, all other terms to the right
x=-16
| 46=4+7w | | 11*x=130 | | 2x-3(3x-1)=-30 | | t/4–7=3 | | -2x+4x=-6 | | -7(1+1x)=70 | | 19h=O | | d/5+19=21 | | 5(2x+7)=-50+45 | | -10-3m=2-6m | | 7j^2+60j-27=0 | | y+30=y-30 | | 3x=5-2(3=4x) | | 0=-3(x-1) | | 9(h+10)=-99 | | x+x+2+3+x=122221 | | y-5/6=-1 | | 4x+-2x=10 | | 2(3^x)-4=14 | | 6(s-82)=84 | | x+9/3=7 | | –19d−d−–12d+6d+–20=4 | | 6/7=2/7x | | (–19d)−d−(–12d)+6d+(–20)=4 | | -3(x-12)=7 | | 4340=35(p+40) | | 100-x=44 | | +5+2m=-2+m | | 6(4^x+9^x)=13.6^x | | (s-69)/8=2 | | 4340=35(p | | 13=z+11 |